Decision Tree‐PLS (DT‐PLS) algorithm for the development of process: Specific local prediction models. (25th April 2019) - Narayanan, Harini; Sokolov, Michael; Butté, Alessandro; Morbidelli, Massimo
Abstract: This work presents a novel multivariate statistical algorithm, Decision Tree‐PLS (DT‐PLS), to improve the prediction and understanding of dynamic processes based on local partial least square regression (PLSR) models for characteristic process groups defined based on Decision Tree (DT) analysis. The DT‐PLS algorithm is successfully applied to two different cell culture data sets, one obtained from bioreactors of 3.5 L lab scale and the other obtained from the 15 ml ambr microbioreactor system. Substantial improvement in the predictive capabilities of the model can be achieved based on the localization compared to the classical PLSR approach, which is implemented in the commercially available packages. Additionally, the differences in the model parameters of the local models suggest that the governing process variables vary for the different process regimes indicating the different states of the cell under different process conditions.